THE URGENCY OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE MANAGEMENT IN RESPONDING TO THE CHALLENGES OF THE TIMES - Dzakaaul, Muhammad Dzakaaul Fikri; Gloria, Ria Yulia; Nadiyah, Azka Nailupar; Ashaffa, Syafiq Hisyam (STAI Ma'had Aly Al-Hikam Malang, 2025)
Education is not only about learning and skills but also a planned effort to develop the individual. The success of education is highly dependent on the effectiveness of the learning process which is influenced by various factors, including the availability of adequate facilities and infrastructure. Infrastructure is a supporting facility that is not used directly, such as classrooms, laboratories, and libraries, while educational facilities are tools and equipment used directly in the teaching and learning process, including computers, books, and stationery. Ensuring a smooth teaching and learning process requires efficient management of infrastructure and facilities. This includes planning, inventorying, structuring, utilization, maintenance and periodic elimination. Using the literature study methodology, this research gathered information from various sources, including books, journals, and other relevant references. The findings of this study highlight the importance of managing infrastructure and facilities well to facilitate an efficient teaching and learning process. Good management is expected to overcome the challenges in managing school facilities and contribute optimally to the education process. Keywords: Education Management; Facilities and Infrastructure; Management of Facilities and Infrastructure. Abstrak Pendidikan tidak hanya mencakup tentang pembelajaran dan keterampilan, tetapi juga merupakan Upaya terencana untuk mengembangkan individu secara menyeluruh. Hal ini meliputi peneneman nilai-nilai dan asimilasi pengetahuan untuk membentuk pribadi yang utuh, keberhasilan Pendidikan sangat bergantung pada efektivitas proses pembelajaran yang dipengaruhi oleh berbagai factor, termasuk ketersedian sarana dan prasarana yang memadai. Prasarana adalah sarana penunjang yang tidak digunakan secara langsung, seperti ruang kelas, laboratorium, dan perpustakaan, sedangkan sarana pendidikan adalah alat dan perlengkapan yang digunakan langsung dalam proses belajar mengajar, antara lain komputer, buku, dan alat tulis. Menjamin kelancaran proses belajar mengajar memerlukan pengelolaan infrastruktur dan fasilitas yang efisien. Hal ini mecakup perencanaan, inventarisasi, penataan, pemanfaatan, pemeliharaan dan penghapusan secara berkala. Dengan menggunakan metodologi studi literatur, penelitian ini mengumpulkan informasi dari berbagai sumber, antara lain buku, jurnal, dan referensi terkait lainnya. Temuan studi ini menyoroti betapa pentingnya mengelola infrastruktur dan fasilitas dengan baik untuk memfasilitasi proses belajar mengajar yang efisien. Manajemen yang baik diharapkan dapat mengatasi tantangan dalam pengelolaan fasilitas sekolah dan memberikan kontribusi optimal bagi proses Pendidikan. Kata Kunci: Manajemen Pendidikan; Sarana dan Prasarana; Pengelolaan Sarana dan Prasarana.